Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Answer:
x = - 3
Step-by-step explanation:
To find the zero, let f(x) = 0, that is
4x + 12 = 0 ( subtract 12 from both sides )
4x = - 12 ( divide both sides by 4 )
x = - 3 ← is the zero
Solve the equation for
x
, when
f
(
x
)
=
0
Then,
x
=
3
.
Explanation:
I assume you mean to find the solution/root (radical)
x
, when
f
(
x
)
=
0
.
Then, this is simple.
Just set
f
(
x
)
to 0 and solve the equation for
x
:
f
(
x
)
=
4
x
−
12
=
0
First we can add 12 on both sides of the equality:
4
x
−
12
+
12
=
0
+
12
which becomes
4
x
=
12
We can now divide both sides of the equality by 4:
4
x
4
=
12
4
and we have
x
=
3
The "zero", or the solution for
f
(
x
)
=
0
is
x
=
3
.
Q.E.D.
x
, when
f
(
x
)
=
0
Then,
x
=
3
.
Explanation:
I assume you mean to find the solution/root (radical)
x
, when
f
(
x
)
=
0
.
Then, this is simple.
Just set
f
(
x
)
to 0 and solve the equation for
x
:
f
(
x
)
=
4
x
−
12
=
0
First we can add 12 on both sides of the equality:
4
x
−
12
+
12
=
0
+
12
which becomes
4
x
=
12
We can now divide both sides of the equality by 4:
4
x
4
=
12
4
and we have
x
=
3
The "zero", or the solution for
f
(
x
)
=
0
is
x
=
3
.
Q.E.D.
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.